Adsorption of Indigo Carmine Dye using Cetyltrimethylammonium Bromide (CTAB) Surfactant Modified Zeolite - Fauziyah, Nurul; Sriatun, Sriatun; Pardoyo, Pardoyo (JURNAL SAINS DAN MATEMATIKA, 2015)
Research of indigo carmine dye adsorption using natural zeolite modified by cetyltrimethylammonium bromide (CTAB) surfactant has been done. The purpose of this study was to modify the natural zeolite using CTAB surfactant and to determine its ability on the adsorption of indigo carmine dye. The stages of the study included the activation of zeolites, modifying zeolites using CTAB surfactant and adsorption test of indigo carmine dye. The results showed that the zeolites could be modified by CTAB. They were then characterized by the existence of FTIR absorption band at wavelengths of 1404.18 cm-1 and 2800-3000 cm-1. The various concentration of indigo carmine (5, 10, 15, 20 ppm); contact time (15, 30, 45 minutes) and pH (3, 4, 5, 6, 7, 8, 9) were studied and the highest condition was reached at the 45 minutes, pH= 3 and indigo carmine concentration of 20 ppm for 0.5 and 1 mM CTAB (15.35% and 23%) and indigo carmine concentration of 5 ppm for 10 mM CTAB (96.18%). The adsorption of indigo carmine tended to increase with increasing the concentration and contact time and decreased with increasing the pH.